A87Sr optical lattice clock with 2.9 × 10 −17 uncertainty and its absolute frequency measurement. (6th May 2021) - Lin, Yige; Wang, Qiang; Meng, Fei; Cao, Shiying; Wang, Yuzhuo; Li, Ye; Sun, Zhen; Lu, Bingkun; Yang, Tao; Lin, Baike; Zhang, Aimin; Fang, Fang; et al.
Abstract: We report the 87 Sr optical lattice clock at NIM with a clock laser referenced to a 30 cm ULE cavity. Several improvements, such as the atomic temperature and density, the lattice laser frequency stabilization, the fiber noise cancellation, etc, have been made since its first evaluation in 2015. Its systematic frequency shifts are carefully evaluated with a total relative uncertainty of 2.9 × 10 −17 . The measured absolute frequency is 429, 228, 004, 229, 873.07(0.13) Hz with a relative uncertainty of 3.1 × 10 −16, with reference to the ensemble of primary and secondary frequency standards published in the Circular T bulletin by BIPM through a satellite link.